Aluminum-based inner grooved heat transfer tube and its manufacturing method

By spraying Zn on the outer surface of the Al-based heat exchange tube and rolling to form an inclination groove, combined with heat treatment and cooling technology, the problem of insufficient corrosion protection and heat exchange performance of the Al-based heat exchange tube is solved, and efficient corrosion protection and heat exchange performance are achieved.

JP7627936B2Active Publication Date: 2025-02-07NJT COPPER TUBE CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021035116
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-05
Publication Date
2025-02-07
Estimated Expiration
2041-03-05

AI Technical Summary

Technical Problem

The existing Al-based heat exchange tubes with grooved inner surfaces have shortcomings in corrosion protection and heat exchange performance, especially in the case of uneven thickness and distribution of Zn diffusion layer, resulting in local corrosion and reduced pressure resistance.

Method used

Using Al-based material, a diffusion layer is formed by spraying Zn on the outer surface of the tube, and an inner surface groove with an inclination angle of 30°-45° is formed by rolling processing. Combined with appropriate heat treatment and cooling processes, a uniform Zn diffusion layer and a fibrous crystal structure are formed to improve corrosion protection and heat exchange performance.

Benefits of technology

The high-efficiency corrosion protection and heat exchange performance of Al-based heat exchange tubes is achieved, which extends the service life and improves the pressure resistance and fatigue strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007627936000001
    Figure 0007627936000001
  • Figure 0007627936000002
    Figure 0007627936000002
  • Figure 0007627936000003
    Figure 0007627936000003
Patent Text Reader

Abstract

To provide an Al-based inner-face grooved heat transmission pipe which is excellent in corrosion resistance, favorable in heat exchange performance, and excellent in practicality, and to provide a technique which can manufacture the Al-based inner-face grooved heat transmission pipe so as to be industrially advantageous.SOLUTION: In an inner-face grooved heat transmission pipe made of Al-based materials in which a large number of grooves are formed at a pipe inner face so as to extend while inclining to a pipe axis at a lead angle of 30° to 45°, and fins in a protrusive form are formed between the grooves, a Zn-diffusion layer is formed at a pipe surface layer part by Zn which is spray-coated on a pipe outer face, the Zn-diffusion layer has an average value of a Zn-concentration equal to or higher than 2.0% and equal to or lower than 5.0% on a pipe outer surface, and an average value of a Zn-diffusion depth equal to or deeper than 80 μm and equal to or shallower than 200 μm, and the grooves at the pipe inner face and the fins are formed by rolling processing at a cross section reduction ratio equal to or higher than 40%.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an aluminum-based internally grooved heat transfer tube and a manufacturing method thereof, and more particularly to an aluminum-based internally grooved heat transfer tube having excellent corrosion resistance and suitable for use in various cross fin tube type heat exchangers in refrigeration, air conditioning, hot water supply equipment, etc., and a method for advantageously manufacturing the same. [Background technology]

[0002] Conventionally, heat exchangers that function as evaporators or condensers have been used in air conditioning equipment such as home air conditioners, automotive air conditioners, and packaged air conditioners, as well as refrigerators, and among these, cross fin tube type heat exchangers have been most commonly used in home indoor air conditioners and commercial packaged air conditioners. The cross fin tube constituting such a cross fin tube type heat exchanger is constructed by integrally assembling aluminum (Al) plate fins on the air side and heat transfer tubes on the refrigerant side. In addition, as the heat transfer tube, a so-called inner grooved heat transfer tube has been widely used, in which a number of grooves, for example, a number of spiral grooves extending at a predetermined lead angle with respect to the tube axis are formed on the inner surface, and inner fins of a predetermined height are formed between the grooves.

[0003] Such inner grooved heat transfer tubes have been mainly formed using copper (Cu)-based materials such as copper and copper alloys, but in order to meet the demand for reducing the weight of equipment and the demand for reducing material costs, the practical application of inner grooved heat transfer tubes made of aluminum (Al)-based materials such as aluminum and aluminum alloys is being considered. However, since Al-based materials have inferior corrosion resistance compared to Cu-based materials, inner grooved heat transfer tubes having a two-layer structure in which an Al-Mn-based alloy is used for the inner layer of the tube, while an Al-Zn-based alloy is clad on the outer surface layer of the tube as a sacrificial corrosion protection layer, have been proposed in WO2013-153972 (Patent Document 1), JP2016-164489A (Patent Document 2), and the like.

[0004] Also proposed is an Al alloy sprayed tube in which a Zn-diffused layer is provided by spraying Zn on the outer surface of the Al alloy tube and then performing a Zn diffusion heat treatment, and since the Zn-diffused layer has a lower pitting potential than the Al alloy portion (tube portion) of the tube material in which Zn is not diffused, it exerts a sacrificial corrosion protection effect, thereby protecting the tube material from corrosion and improving the durability life of the tube material. Such Zn spraying can be performed after the process of forming grooves on the inner surface of the heat transfer tube, and can also be performed prior to the groove formation process, but no details have been made public.

[0005] Furthermore, JP 2018-91526 A (Patent Document 3) discloses that a heat transfer tube having inner grooves formed parallel to the tube axis direction by extrusion processing is used, and a streak-like Zn diffusion layer of a predetermined width extending in the tube axis direction is formed on the outer surface of the heat transfer tube, and then a twisting process is performed to process the streak-like Zn diffusion layer on the outer surface of the tube and the grooves on the inner surface of the tube into a spiral shape, thereby producing a heat transfer tube with excellent heat exchange performance and corrosion resistance.

[0006] However, the conventional Al-based internally grooved heat transfer tubes disclosed in the above Patent Documents 1 to 3 etc. have various inherent problems in practical use, and it is difficult to say that they are heat transfer tubes with optimal characteristics.

[0007] Specifically, for example, in the manufacture of an Al-based internally grooved heat transfer tube, when Zn thermal spraying is performed after the inner groove processing, if there are any locations where the surface Zn concentration exceeds 10%, corrosion may be significantly accelerated depending on the usage environment. Furthermore, if the Zn diffusion depth exceeds 200 μm, the Zn concentration gradient from the surface to the thickness direction becomes gentle, and corrosion progresses preferentially in the thickness direction rather than the circumferential direction. Not only does this make the sacrificial corrosion protection effect intended to disperse corrosion in the circumferential direction insufficient, but it also causes localized exposure of the tube material (Al-based material), which reduces the remaining thickness of the tube material due to corrosion, raising concerns that the pressure resistance and fatigue strength required for heat exchangers may be impaired.

[0008] In addition, Patent Document 3, which shows a case where the inner surface groove processing of the heat transfer tube is performed by extrusion or by twisting after extrusion, employs a method of forming an inner spiral grooved tube by repeatedly passing an aluminum alloy extruded raw tube with a plurality of linear grooves formed on the inner surface along the length direction through a drawing die to reduce the diameter and to give a twist, and it is also described that by performing die drawing and twisting after Zn spraying without diffusing Zn, it is possible to scrape off Zn in the part where the Zn amount is locally increased, and to level out the Zn amount. However, there is a problem in that the effect of scraping off the excess Zn adhesion part by spraying is limited. This is because in this method, the lead angle is small, less than 30°, due to the twisting process caused by diameter reduction when passing through the die (it is difficult to form grooves with a lead angle of 30° or more, and there is a limit to the improvement of heat exchange performance), and since plastic flow mainly occurs in the axial direction of the tube, after the tube is removed from the die, the distribution of plastic flow in the circumferential and thickness directions is less than in the axial direction of the tube, and the Zn-shape areas on the sprayed surface immediately after the excess Zn deposition at the die entrance is scraped off basically maintain their concentration differences along with their relative positional relationships even after passing through the die, and for this reason, it cannot be said that the effect of correcting the difference in Zn deposition shade is sufficient.

[0009] Furthermore, as for the chemical components of the Al-based material that is the tube material of the Al-based inner grooved heat transfer tube, the Al alloy used in Patent Document 1 contains 0.3 to 0.8 mass% of Cu as an additive element for the purpose of improving strength, but if the Cu content is 0.10 mass% or more, there is a problem that the self-corrosion resistance of the tube material is significantly reduced, etc. In addition, when most of the Zn diffusion layer of the outer skin, which is a sacrificial corrosion protection layer, disappears, the remaining diffusion layer reduces in volume and the Zn concentration decreases, and as a result, the corrosion protection distance for the exposed tube material cannot be sufficiently secured, for example, when the condensed water generated on the surface of the heat transfer tube or piping that constitutes the heat exchanger partially dries and the conduction between the Zn concentration regions is lost, there is an inherent problem that corrosion origins occur at the points where the sacrificial corrosion protection function is lost, and penetration occurs in a short time in the form of pitting corrosion. Similarly, the Al alloy used in Patent Document 2 is said to contain the additive element Mg in the range of 0.1 to 0.6 mass % for the purpose of improving strength. However, when the Al alloy contains 0.10 mass % or more of Mg, and the outer corrosion protection layer containing Zn is diffusion treated, the dissolved Mg in the Al alloy parent phase constituting the pipe material and the diffused Zn form an intermetallic compound, which significantly reduces the hardening and elongation of the product and causes problems such as breakage during hairpin bending processing. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] WO2013-153972 [Patent Document 2] JP 2016-164489 A [Patent Document 3] JP 2018-91526 A Summary of the Invention [Problem to be solved by the invention]

[0011] The present invention has been made against the background of the above circumstances, and an object of the present invention is to provide an Al-based internally grooved heat transfer tube which has excellent corrosion resistance, good heat exchange performance, and excellent practicality, and also to provide a method for manufacturing such an Al-based internally grooved heat transfer tube in an industrially advantageous manner. [Means for solving the problem]

[0012] In order to solve the above problems, the present invention can be preferably implemented in various aspects as listed below, and each aspect described below can be adopted in any combination. It should be considered that the aspects and technical features of the present invention are not limited to those described below, but are understood based on the inventive idea grasped from the description of the entire specification.

[0013] First, a first aspect of the present invention is an internally grooved heat transfer tube made of an Al-based material, in which a large number of grooves are formed on the inner surface of the tube so as to extend at an inclination with a lead angle of 30° to 45° relative to the tube axis, and fins in the form of protrusions are formed between the grooves, and a Zn diffusion layer is formed on the tube surface layer portion by Zn sprayed on the outer surface of the tube, and this Zn diffusion layer has an average Zn concentration on the outer surface of the tube of 2.0% to 5.0% and an average Zn diffusion depth of 80 μm to 200 μm, and further, the grooves and fins on the inner surface of the tube are formed by rolling with a cross-sectional reduction rate of 40% or more.

[0014] A second aspect of the present invention is characterized in that the tube crystal structure has a recrystallized structure and / or a fibrous structure having an average crystal grain size of 2 μm or more and less than 15 μm.

[0015] Furthermore, a third aspect of the present invention is characterized in that the Al-based material is a 3000 series Al alloy.

[0016] Furthermore, the fourth aspect of the present invention is characterized in that the Cu and Mg contents of the Al-based material are each less than 0.10 mass%, and in addition, the fifth and sixth aspects of the present invention are characterized in that the Al-based material contains 0.10 to 0.30 mass% of Zn or Ti, respectively.

[0017] In order to advantageously obtain an Al-based internally grooved heat transfer tube as described above, the present invention employs, as a seventh aspect, a method for manufacturing an internally grooved heat transfer tube made of an Al-based material, in which a large number of grooves are formed in a spiral shape on the inner surface of the tube and fins having a ridge form are formed between the grooves, the method comprising the steps of: (a) performing a Zn thermal spraying treatment on the outer surface of a mother tube made of an Al-based material, followed by a diffusion heat treatment to form a Zn diffusion layer on the tube surface layer portion; and (b) performing a rolling process on the mother tube made of an Al-based material on which the Zn diffusion layer has been formed, so that the cross-sectional reduction rate is 40% or more, to obtain a rolled tube in which the large number of grooves are formed to extend at an inclination angle of 30° to 45° with respect to the tube axis and fins having a ridge form are formed between the grooves.

[0018] In an eighth aspect of the present invention, the rolling process comprises sequentially carrying out the steps of supporting die drawing, ball diameter reducing groove forming and finishing die drawing.

[0019] Furthermore, a ninth aspect of the present invention is characterized in that the method further comprises a step of subjecting the rolled pipe to an annealing softening treatment.

[0020] In addition, a tenth aspect of the present invention is characterized in that the Al-based internally grooved heat transfer tube according to any one of the first to sixth aspects is manufactured by the above-mentioned manufacturing method. Effect of the Invention

[0021] According to the configuration of the present invention, an Al-based internally spirally grooved heat transfer tube having excellent corrosion resistance and good heat exchange performance can be provided industrially advantageously as a heat transfer tube with excellent practicality by optimizing the state of Zn applied to the tube surface by Zn thermal spraying. Furthermore, such a practical Al-based internally grooved heat transfer tube can be industrially advantageously manufactured. [Brief description of the drawings]

[0022] [Figure 1] FIG. 2 is a process explanatory diagram showing, in cross section, an example of a rolling process employed in the manufacturing method of an Al-based internally grooved heat transfer tube according to the present invention. [Diagram 2] FIG. 2 is an explanatory view showing an enlarged portion of a cross section of an Al-based internally grooved heat transfer tube according to the present invention. [Diagram 3] FIG. 1 is an explanatory view showing the internal configuration of an Al-based internally grooved heat transfer tube according to the present invention, with a portion cut away. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] In short, the aluminum-based internally grooved heat transfer tube according to the present invention can be suitably manufactured by subjecting a circular mother tube made of a predetermined aluminum-based material to a Zn thermal spraying treatment to form a Zn diffusion layer on the surface layer of the tube, and then performing rolling at a large reduction in area, and while various aluminum-based materials made of known aluminum or aluminum alloys can be used as the tube material for the aluminum-based material mother tube, the JIS 3000 series aluminum alloy is particularly advantageously used in the present invention. This 3000 series aluminum alloy has excellent corrosion resistance and workability, and is a material suitable for an internally grooved heat transfer tube.

[0024] Among such 3000 series Al alloys, those containing less than 0.10% by mass of copper (Cu) and magnesium (Mg) are advantageously used. If the Cu content is 0.10% by mass or more, problems such as a significant decrease in the self-corrosion resistance of the pipe material will occur, and if the Mg content is 0.10% by mass or more, problems such as hardening due to the formation of intermetallic compounds, a significant decrease in elongation, and the possibility of breakage during hairpin bending of the pipe will occur.

[0025] Furthermore, it is preferable to incorporate zinc (Zn) and titanium (Ti) in the Al-based material of the above-mentioned pipe material at a ratio of 0.10 to 0.30 mass%. That is, by adding a small amount of Zn, many corrosion starting points can be generated, leading to a uniform corrosion form, and by adding a small amount of Ti, a high Ti concentration region and a low Ti concentration region can be formed in the parallel cross-sectional thickness direction after extrusion, and these can be distributed in layers alternately in the thickness direction. As a result, the Al-Zn part on the outer surface acts as a corrosion trigger on the pipe surface, and corrosion is propagated preferentially to the low Ti concentration region in the thickness direction, and the corrosion form progresses in layers in the longitudinal and circumferential directions, so that the progress of corrosion in the thickness direction can be suppressed, and thus the pitting corrosion resistance, intergranular corrosion resistance, and crevice corrosion resistance can be advantageously improved.

[0026] In the present invention, the outer surface of the blank tube made of such an Al-based material is sprayed with Zn in the same manner as in the past, specifically, by spraying Zn using a two-gun or three-gun method to form a Zn sprayed layer on the outer surface of the tube, and then the diffusion process is performed by diffusing Zn from the sprayed Zn layer into the tube material by heat treatment, thereby forming the desired Zn diffusion layer on the tube surface. The formation of such a Zn diffusion layer results in a layer of Zn having a lower corrosion potential than the Al of the tube material being formed on the outer surface, which effectively provides a sacrificial protection effect, realizes a uniform corrosion form from the outer surface, prevents early occurrence of localized pitting corrosion or intergranular corrosion, and significantly extends the penetration life. Here, the Zn diffusion layer refers to a portion having a higher Zn concentration than the tube material, and generally refers to a portion having a Zn concentration higher than the Zn concentration of the tube material by about 0.20 mass % or more.

[0027] Next, the Al-based material raw tube with the Zn diffusion layer formed thereon is subjected to a rolling process with a cross-sectional reduction rate of 40% or more, and a large number of inner surface grooves are formed extending at an inclination with a lead angle of 30° to 45° relative to the tube axis, and fins with a ridge shape are formed between these grooves, thereby forming the desired Al-based inner surface grooved heat transfer tube.

[0028] By adjusting the lead angle α of the grooves formed by such rolling to 30° or more, particularly to a high lead angle exceeding 35°, it is possible to scrape off the excess Zn deposition on the surface of the Zn sprayed bare tube and promote homogenization of the Zn sprayed surface over the entire circumference, and by promoting plastic flow in the tube axis (L), circumferential (θ) and wall thickness (T) directions by utilizing the strong processing by rolling, it is possible to create a substantial correction effect after rolling for the difference in Zn deposition density on the surface in the L and θ directions and the Zn diffusion layer thickness distribution in the θ and T directions in the bare tube state that has been subjected to Zn spraying and diffusion heat treatment. Here, if the lead angle α exceeds 45°, the angle of the plastic flow when the fins are formed on the inner surface of the tube becomes too large with respect to the tube axis direction, and resistance increases significantly, which causes breakage of the material and makes rolling difficult. Furthermore, if the processing speed is limited to an extremely low speed in order to avoid such a problem, this will result in an increase in processing costs.

[0029] In addition, in such rolling, various rolling methods known as the well-known roll rolling method and ball rolling method can be appropriately adopted. In the present invention, in particular, a rolling method consisting of sequentially carrying out the steps of supporting die drawing, ball reducing groove forming, and finishing die drawing is advantageously adopted, an example of which is shown diagrammatically in FIG. 1.

[0030] 1, an Al-based material tube 10 having a Zn diffusion layer formed thereon is drawn to a predetermined outer diameter by being passed through support dies 12 in sequence, and a plurality of (e.g., four) rolling balls 16 are disposed between the support dies 12 and finishing dies 14 around the outer periphery of the tube to compress the outer periphery of the tube and reduce the diameter, while a spiral groove plug 18 having a spiral groove formed on its outer periphery is disposed inside the tube, and the inner surface of the tube is pressed against the outer periphery of the spiral groove plug 18 by the pressing (diameter reduction) action of the rolling balls 16 to form a groove with a predetermined lead angle α on the inner surface of the tube, and then a rolled tube 20 is taken out as an Al-based internally grooved heat transfer tube having a final outer diameter by the finishing dies 14. The spiral groove plug 18 can be held by a mandrel 24 so as to be freely rotatable relative to a support plug 22 held by the support dies 12.

[0031] Furthermore, the rolled tube 20, which is an Al-based inner surface grooved heat transfer tube obtained by such rolling processing, has a structure in which a plurality of spiral grooves 26 are formed on its inner surface by grooving processing using the spiral groove plug 18, as shown in Fig. 2, and fins 28 in the form of protrusions are formed at a predetermined height: H between the spiral grooves 26, 26. The plurality of spiral grooves 26 are formed in a form that has a predetermined lead angle: α, as shown in Fig. 3. The wall thickness of the rolled tube 20 is indicated as T.

[0032] By performing such rolling, a strong groove processing with a cross-sectional area reduction rate of 40% or more is performed, so that the excess Zn adhesion portions present on the surface of the Zn sprayed bare pipe are effectively scraped off, and by utilizing this strong rolling processing to promote plastic flow in the tube axis (L direction), circumferential (θ direction) and wall thickness (T) directions, the difference in Zn adhesion on the surface in the L and θ directions and the thickness distribution width of the Zn diffusion layer in the θ and T directions that occurs in the bare pipe state after Zn spraying and diffusion heat treatment are substantially corrected after rolling, reducing the difference in Zn and the Zn diffusion distribution width, thereby effectively improving corrosion resistance. Note that due to the above-mentioned action of this rolling process, even if the Zn diffusion layer at the rolled bare pipe stage is relatively thin, improvement in corrosion resistance can be advantageously realized in the state after rolling.

[0033] In the Al-based inner grooved heat transfer tube (20) obtained in this way, the average Zn concentration on the outer surface of the tube is adjusted to be 2.0 mass% or more and 5.0 mass% or less, and the average Zn diffusion depth in the Zn diffusion layer is adjusted to be 80 μm or more and 200 μm or less. This is because, when the average surface Zn concentration is less than 2.0 mass%, due to the nature of the thermal spraying technology, the proportion of parts where the Zn concentration on the outer surface is extremely low increases, making it difficult to expect a uniform sacrificial protection effect, and corrosion is likely to progress in the thickness direction in the parts with low Zn concentration, resulting in early penetration in a pitting state. In addition, when the average surface Zn concentration exceeds 5.0 mass%, similarly, there are likely to be parts with extremely high Zn concentration on the tube surface, which creates the inherent problem of significantly accelerating corrosion in those parts.

[0034] In addition, even if the Zn diffusion depth is less than 80 μm, the diffusion of Zn sprayed on the outer surface is shallow, the Zn concentration remaining near the surface is maintained high, and the Zn concentration gradient in the wall thickness direction becomes large, so that the corrosion progresses in the circumferential direction, but the total volume of the Zn diffusion layer is insufficient, so that the corrosion protection function is lost in a relatively short time, and pitting corrosion occurs in the exposed pipe material, leading to a problem of penetration. On the other hand, if the Zn diffusion depth exceeds 200 μm, the Zn concentration gradient from the pipe surface to the wall thickness direction becomes gentle, so that the corrosion progresses in the wall thickness direction rather than the circumferential direction, and not only is the sacrificial corrosion protection effect intended to disperse corrosion in the circumferential direction insufficient, but the pipe material (Al-based material) is exposed locally, so that as the corrosion progresses, the remaining thickness of the pipe material becomes thin, and there is a concern that the pressure resistance and fatigue strength required for heat exchangers will be impaired.

[0035] Furthermore, the thus obtained Al-based internally grooved heat transfer tube (20) desirably has a recrystallized structure with an average grain size of 2 μm or more and less than 15 μm, and / or a fibrous structure, and by adopting such a heat transfer tube crystal structure, it exhibits the characteristic of being able to significantly improve self-corrosion resistance even after the Zn diffusion layer for sacrificial corrosion protection is completely consumed. Here, the fibrous structure is recognized as a structure in which dislocations are concentrated at a high density in crystal grains that have been stretched by plastic processing applied during hot or cold working.

[0036] In order to obtain such a crystal structure of a heat transfer tube, a high-frequency induction heating device is used in the annealing softening treatment adopted as the final heat treatment process of the Zn sprayed rolled tube as described above to control the heat input, thereby controlling the driving force for recrystallization of the Zn sprayed rolled tube, and immediately thereafter, instantaneous cooling by water cooling is performed to suppress segregation of intermetallic compounds between the base material and impurities. This can be achieved.

[0037] If the average grain size of the recrystallized structure of such a heat transfer tube is less than 2 μm, the proportion of processed structure remaining increases, making it difficult to ensure an elongation of 30% or more, which is required for hairpin bending and tube expansion of the product. Also, if the average grain size is 15 μm or more, the peak concentration of intermetallic compounds such as Al-Mn, Al-Si, Al-Cu, etc., which segregate to the recrystallized grain boundaries during the annealing and cooling process increases, causing problems such as an increased susceptibility to intergranular corrosion and a decrease in the self-corrosion resistance of the tube material.

[0038] The aluminum-based internally grooved heat transfer tube according to the present invention having such characteristics can be advantageously used as a heat transfer tube in cross fin tube type heat exchangers for various applications that have been conventionally known, such as refrigerators, air conditioners, and hot water heaters.

[0039] Although the representative embodiments of the present invention have been described above in detail, it should be understood that they are merely examples, and the present invention should not be interpreted in any limited manner by the specific description of such embodiments. The present invention can be implemented in various forms with various changes, modifications, improvements, etc., based on the knowledge of those skilled in the art, and it goes without saying that all such implementation forms belong to the scope of the present invention as long as they do not deviate from the gist of the present invention. EXAMPLES

[0040] Representative examples of the present invention will be presented below to clarify the features of the present invention in more detail. However, it should be understood that the present invention is not limited in any way by the description of such examples.

[0041] First, a 3000 series Al alloy ingot consisting of 0.03% by mass of Si, 0.05% by mass of Fe, 0.001% by mass of Cu, 0.001% by mass of Cr, 0.7% by mass of Mn, 0.001% by mass of Mg, 0.15% by mass of Zn, 0.15% by mass of Ti, impurities: 0.05% by mass or less each (total 0.15% by mass or less), and the balance being Al, was cast by a continuous casting method, and the resulting billet was subjected to homogenization treatment, and the billet shaped to a size of 200 mmφ was heated to 400 to 450°C by in-line induction heating, and an extruded tube with an outer diameter of 18 mmφ and a wall thickness of 1.0 mm was obtained by a porthole extrusion method. Note that this extruded tube was formed into a long coil of 1000 m or more by continuously extruding a plurality of billets in the extrusion method. Thereafter, the long coil was unwound and subjected to two passes of die drawing to form a blank tube having an outer diameter of 10 mm and a wall thickness of 0.65 mm.

[0042] Next, the long coil of the blank tube was continuously unwound and heated to 400°C or higher in a high-frequency induction heating device, after which Zn was sprayed in-line from two directions, one above and one below, and then water-cooled and air-dried, and the tube was wound up again into a long coil. That is, the Zn spraying conditions were a two-gun method, and the conditions for Zn wire feed, spraying current, air nozzle, etc. were set so that a Zn sprayed surface with a concentration of 0.35 mass% or more was formed on the outer surface of the tube, and the coverage rate was 80% or more.

[0043] The Zn-sprayed long coil was then placed in a batch annealing furnace and subjected to a Zn diffusion heat treatment by increasing the temperature at a rate of 50°C / hr or more, reaching a temperature of 450°C, and holding for 5 hours, followed by cooling at a rate of 5 to 10°C / hr. As a result, a Zn diffusion layer, i.e., a sacrificial anticorrosion layer, was formed on the surface layer of the long coil (bare pipe), and a Zn-sprayed raw pipe for the following rolling process was obtained.

[0044] Next, rolling was performed to form a predetermined groove on the inner surface of the thus obtained Zn sprayed base tube. Specifically, the rolling process was performed according to the rolling process shown in Fig. 1, in which a support plug 22 and a spiral groove plug 18 were connected by a mandrel 24, and the resulting product was inserted into the Zn sprayed base tube 10, and grooves were formed on the inner surface of the tube by drawing with the support die 12 and compressive grooving with the rolling ball 16, and then finish forming was performed through the finishing die 14 to obtain a rolled tube (inner grooved heat transfer tube) 20 with an outer diameter D of 7 mm, a bottom wall thickness T of 0.47 mm, a fin height H of 0.22 mm, number of fins: 55, a fin apex angle β of 18°, a lead angle α of 40°, and a unit weight W of 32 g / m. In addition, when forming the obtained rolled tube 20, the cross-sectional area reduction rate from the base tube 10 was 41.1%. In addition, the reduction rate of the bottom wall thickness of the rolled pipe 20 relative to the average wall thickness of the mother pipe 10 was 27.7%.

[0045] Finally, the rolled tube 20 thus obtained was subjected to an annealing softening treatment as a final heat treatment step. Specifically, the annealing softening treatment was performed by heating the tube to a temperature of 350°C or higher in-line using a high-frequency induction heating device, immediately followed by water cooling, air blow drying, and winding into a long coil. In the annealing step of the rolled tube 20, the recrystallization driving force of the rolled tube was controlled by controlling the heating coil input of the induction heating device, and the segregation of intermetallic compounds between the base material and impurities was suppressed by instantaneous cooling with water cooling, thereby making it possible to obtain a crystal structure including a fiber structure with an average crystal grain size of the recrystallized structure in the range of 2 μm or more and less than 15 μm.

[0046] -Performance evaluation- The following tests were carried out to evaluate the properties of the Zn sprayed bare pipe and the inner grooved pipe (rolled pipe) obtained above.

[0047] (a) Average grain size A test piece for microstructure observation was cut out from the obtained inner grooved pipe, and the average crystal grain size of the recrystallized structure was measured. Specifically, the average crystal grain size was measured in two directions, the thickness direction and the circumferential direction of the pipe, using the intersection line method, and the average value was calculated. As a result, the average crystal grain size of the recrystallized structure was 8 μm, which is within the range of 2 μm to less than 15 μm, and a crystal structure with the effect of improving self-corrosion resistance was obtained.

[0048] (b) Measurement of Zn concentration on the outer surface of the tube and Zn diffusion depth in the tube surface layer The Zn concentration and Zn diffusion depth on the outer surface of the Zn sprayed raw pipe and the inner grooved heat transfer pipe (rolled pipe) were measured by EPMA as follows.

[0049] Specifically, regarding the surface Zn concentration, a 20 mm long tube sample was cut along the tube axis and fully stretched into a flat plate. After that, EPMA line analysis was performed at three locations in the tube axis direction on the Zn-sprayed surface at 25 μm intervals in the width direction, at least 5 mm away from the cut end in the tube axis direction, to measure the Zn concentration, and the results were averaged.

[0050] Regarding the Zn diffusion depth, eight locations with a phase difference of 45° in the circumferential direction of the tube were selected on the cross section of the tube sample perpendicular to the tube axis, and EPMA line analysis was performed at 1 μm intervals in the thickness direction from the outer surface of each location. The distance at which a Zn concentration of 0.35 mass% or more was measured was defined as the Zn diffusion distance (Zn diffusion depth).

[0051] Measurement results for Zn sprayed raw pipes For the Zn diffusion layer where the Zn concentration obtained by the Zn diffusion treatment is 0.35 mass% or more, the diffusion distance in the wall thickness direction was measured as 100±30μm as the average value of 8 circumferential points. Meanwhile, the Zn concentration on the tube surface was in the range of 4.0-8.0 mass% as the average value of the same 8 points, but the localized Zn concentration peak value measured at 0.05mm intervals over the entire circumferential direction was confirmed to reach a maximum of 18 mass%.

[0052] Measurement results for inner grooved heat transfer tubes For an inner grooved pipe (Zn-sprayed rolled pipe) obtained by rolling a Zn-sprayed bare pipe, the diffusion distance in the wall thickness direction where the Zn concentration was 0.2 mass% or more was measured to be 120±20μm on average at eight circumferential points. Meanwhile, for the surface Zn concentration, the average value of the eight same positions was in the range of 3.0-4.0 mass%, but the localized Zn concentration peak value measured at 0.05mm intervals over the entire circumferential direction was confirmed to reach a maximum of 8.0 mass%. [Explanation of symbols]

[0053] 10 Zn sprayed base tube 12 Support die 14 Finishing die 16 Rolling ball 18 Spiral groove plug 20 Rolled tube (Al-based inner grooved heat transfer tube) 22 support plug 24 mandrel 26 Spiral groove 28 Fin

Claims

1. The present invention provides an inner grooved heat transfer tube made of an Al-based material, which is made of a 3000 series Al alloy having a Cu content of less than 0.10% by mass, and which has a number of grooves formed on the inner surface of the tube so as to extend at an inclination with respect to the tube axis at a lead angle of 30° to 45°, and has fins having a protruding shape formed between the grooves, the Cu content being less than 0.10% by mass, An aluminum-based internally grooved heat transfer tube, characterized in that a Zn diffusion layer is formed on the tube surface layer by Zn sprayed on the outer surface of the tube, and the Zn diffusion layer has an average Zn concentration on the outer surface of the tube of 2.0 mass% or more and 5.0 mass% or less and an average Zn diffusion depth of 80 μm or more and 200 μm or less, and further, grooves and fins on the inner surface of the tube are formed by rolling processing the tube material on which the Zn diffusion layer is formed, with a cross-sectional reduction rate of 40% or more.

2. 2. The aluminum-based internally grooved heat transfer tube according to claim 1, characterized in that the tube crystal structure has a recrystallized structure having an average crystal grain size of 2 μm or more and less than 15 μm and / or a fibrous structure.

3. An Al-based internally grooved heat transfer tube as described in claim 1 or claim 2, characterized in that the lead angle is a high lead angle exceeding 35°.

4. 4. The aluminum-based internally grooved heat transfer tube according to claim 1, wherein the aluminum-based material has an Mg content of less than 0.10 mass %.

5. 5. The aluminum-based inner grooved heat transfer tube according to claim 1, wherein the aluminum-based material contains 0.10 to 0.30 mass % of Zn.

6. 6. The aluminum-based internally grooved heat transfer tube according to claim 1, wherein the aluminum-based material contains 0.10 to 0.30 mass % of Ti.

7. A method for manufacturing an aluminum-based internally grooved heat transfer tube having a large number of grooves formed in a spiral shape on the inner surface of the tube and fins having a ridge shape formed between the grooves, comprising the steps of: a step of using an Al-based material tube made of a 3000-series Al alloy having a Cu content of less than 0.10% by mass, performing a Zn thermal spraying treatment on an outer surface of the tube, and then performing a diffusion heat treatment to form a Zn diffused layer on the tube surface layer portion; a rolling process is performed on the aluminum-based material tube having the Zn-diffused layer formed thereon, with a cross-sectional area reduction rate of 40% or more, to obtain a rolled tube in which the numerous grooves are formed to extend at an inclination with respect to the tube axis at a lead angle of 30° to 45° and in which fins having a ridge shape are formed between the grooves; A method for manufacturing an aluminum-based internally grooved heat transfer tube, comprising the steps of:

8. The method for manufacturing an aluminum-based internally grooved heat transfer tube according to claim 7, characterized in that the rolling process comprises sequentially carrying out the steps of supporting die drawing, ball reducing groove forming and finishing die drawing.

9. The method for producing an aluminum-based internally grooved heat transfer tube according to claim 7 or 8, further comprising a step of subjecting the rolled tube to an annealing softening treatment.

10. 10. A method for producing an aluminum-based internally grooved heat transfer tube according to claim 7, wherein the aluminum-based internally grooved heat transfer tube is the aluminum-based internally grooved heat transfer tube according to claim 1.

Citation Information

Patent Citations

  • Tube with grooved inner face and method for manufacturing it

    JP2003290816A

  • Heat transfer pipe with aluminum alloy-based inner surface groove

    JP2016164489A

  • Heat transfer pipe, heat exchanger, and method for manufacturing heat transfer pipe

    JP2018091526A

  • Heat exchange tube attached with aluminum alloy inner groove

    WO2013153972A1